2019
DOI: 10.1016/j.healthplace.2019.102150
|View full text |Cite
|
Sign up to set email alerts
|

Hukou system, mechanisms, and health stratification across the life course in rural and urban China

Abstract: The literature on rural-urban health disparities have mostly focused on de facto rural/urban differences, and its intersections with de jure rural-urban divide are less understood. This research provides a comprehensive investigation of how the intersection of rural\urban residence and rural \urban household registration (hukou) status is associated with a range of health outcomes in later life. We investigate major mechanisms in accounting for these health disparities across the life span. Results show that r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
87
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(90 citation statements)
references
References 33 publications
2
87
1
Order By: Relevance
“…Liu found that agricultural hukou holders often have fewer educational resources, lower rates of return on education, and limited employment choice in inflow cities [ 1 ]. Song and Smith suggested that the health inequalities between non-agricultural and agricultural hukou holders can be attributed to the differences in medical services and family backgrounds since childhood and the lower number of clean water resources in rural areas than in urban areas [ 5 ]. In the past decade, the resource allocation effect exerted by the Internet has likely interacted with the hukou system and had different effects on the psychological well-being of non-agricultural and agricultural hukou holders.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu found that agricultural hukou holders often have fewer educational resources, lower rates of return on education, and limited employment choice in inflow cities [ 1 ]. Song and Smith suggested that the health inequalities between non-agricultural and agricultural hukou holders can be attributed to the differences in medical services and family backgrounds since childhood and the lower number of clean water resources in rural areas than in urban areas [ 5 ]. In the past decade, the resource allocation effect exerted by the Internet has likely interacted with the hukou system and had different effects on the psychological well-being of non-agricultural and agricultural hukou holders.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, this system often places agricultural hukou holders at a disadvantage in terms of access to resources such as education, housing, and social security [ 1 , 2 ]. Many scholars have noted that the differences in social welfare hidden behind the hukou system have an adverse effect on the subjective well-being, physical health, and psychological well-being of agricultural hukou holders [ 3 , 4 , 5 , 6 , 7 , 8 ], and they have provided helpful insights into understanding the differences in subjective well-being between Chinese agricultural and non-agricultural hukou holders.…”
Section: Introductionmentioning
confidence: 99%
“…SES conventionally included three indicators of educational attainment, household income, and employment status. Some researchers indicated that Hukou status should be included in the SES, as it dictated the social bene ts a person received in China [33][34][35]. Hukou system (also called household registration system) of China classi ed all residents into rural and urban holders.…”
Section: Independent Variablesmentioning
confidence: 99%
“…Some researchers indicated that Hukou status should be included in the SES, as it dictated the social benefits a person received in China [27][28][29]. Therefore, this study used educational attainment (Illiteracy, Primary school degree, Junior high school degree, high school degree, and university degree or above); household income, employment status (employed, unemployed), and Hukou status (urban or rural) to measure SES of the women.…”
Section: Independent Variablesmentioning
confidence: 99%